Prefrontal Dopaminergic Mechanisms of Extinction in Adolescence Compared to Adulthood in Rats - Zbukvic, Isabel C.; Park, Chun Hui J.; Ganella, Despina E.; Lawrence, Andrew J.; Kim, Jee Hyun (Frontiers in Behavioral Neuroscience, 2017)
Adolescents with anxiety disorders attain poorer outcomes following extinction-based treatment compared to adults. Extinction deficit during adolescence has been identified to involve immaturity in the medial prefrontal cortex (mPFC). Findings from adult rodents suggest extinction involves dopamine signaling in the mPFC. This system changes dramatically during adolescence, but its role in adolescent extinction is unknown. Therefore, we investigated the role of prefrontal dopamine in extinction using Pavlovian fear conditioning in adolescent and adult rats. Using quantitative PCR analyses, we measured changes in dopamine receptor gene expression in the mPFC before and after extinction. We then enhanced dopamine 1 receptor (D1R) or dopamine 2 receptor (D2R) signaling in the infralimbic cortex (IL) of the mPFC using agonists at the time of extinction. Adolescent rats displayed a deficit in extinction retention compared to adults. Extinction induced a reduction in D1R compared to D2R gene expression in adolescent rats, whereas an increase of D1R compared to D2R gene expression was observed in adult rats. Acutely enhancing IL D1R signaling using SKF-81297 had no effect on extinction at either age. In contrast, acutely enhancing IL D2R signaling with quinpirole significantly enhanced long-term extinction in adolescents, and impaired within-session extinction in adults. Our results suggest a dissociated role for prefrontal dopamine in fear extinction during adolescence compared to adulthood. Findings highlight the dopamine system as a potential pharmacological target to improve extinction-based treatments for adolescents.